A silver bullet for ageing medicine?: clinical relevance of T-cell checkpoint receptors in normal human ageing - Rimmer, Lucy; Mann, Derek A.; Sayer, Avan A.; Amarnath, Shoba; Granic, Antoneta (Frontiers in Immunology, 2024)
Immunosenescence describes dysregulation of the immune system with ageing manifested in both the innate and adaptive immunity, including changes in T-cell checkpoint signalling. Through complex and nuanced process, T-cells lose excitatory signalling pathways and upregulate their inhibitory signalling, leading to ineffective immune responses that contribute to the formation of the ageing phenotype. Here we expand on the expression, function, and clinical potential of targeting the T-cell checkpoint signalling in age and highlight interventions offering the most benefits to older adults' health. Notably, modifications in vaccination such as with mTOR inhibitors show immediate clinical relevance and good tolerability. Other proposed treatments, including therapies with monoclonal antibodies fail to show clinical efficacy or tolerability needed for implementation at present. Although T-cell co-signalling fits a valuable niche for translational scientists to manage immunosenescence, future study would benefit from the inclusion of older adults with multiple longterm conditions and polypharmacy, ensuring better applicability to actual patients seen in clinical settings.